Immunosuppressive Serum Factors in Patients with Dermatophytoses - Hafidh R. Rand; Abdul Muhaimen Nidhal; Dabbagh Rasool (College of Pharmacy / Mustansiriyah University, 2005)
Serum factors may be involved in suppression of cell-mediated immunity to fungal antigens in chronic dermatophytoses. In certain cases like dermatophytoses, the infectious process may generate a serum factor that is capable of inducing immunosuppression, thereby the patient susceptible to chronic infection. Lymphocytes isolated from heparinized whole blood of fifteen patients and fifteen control subjects were used in order to prepare a pure population, ready for use in microculture tetrazolium (MTT) assay to measure the proliferative activity of PBL in patients and control subjects. Lymphocytes were isolated by density gradient sedimentation. Non-significant differences (P>0.05) revealed when the patients sera incubated with its own lymphocytes and with controls lymphocytes. The study found that absence of the serum inhibitory factors with specific and/or non-specific action in patients sera may be associated with the local rather than the systemic action of dermatophytederived lymphocyte inhibitory factors. The study also found that patients sera were with stimulatory rather than inhibitory action.